Diagnosis and treatment of latent tuberculosis in patients with multiple sclerosis, expert consensus. On behalf of the Colombian Association of Neurology, Committee of Multiple Sclerosis (2018)
ABSTRACT: Background: Multiple sclerosis is an inflammatory and neurodegenerative demyelinating disease. Current treatment of multiple sclerosis focuses on the use of immunomodulatory, immunosuppressant, and selective immunosuppressant agents. Some of these medications may result in high risk of opportunistic infections including tuberculosis. Objective: The purpose of this study was to obtain consensus from a panel of neurologists, pulmonologists, infectious disease specialists, and epidemiology experts regarding the diagnosis, treatment, and monitoring of latent tuberculosis in patients with multiple sclerosis. Methods: A panel of experts in multiple sclerosis and tuberculosis was established. The methodological process was performed in three phases: definition of questions, answer using Delphi methodology, and the discussion of questions not agreed. Results: Tuberculosis screening is suggested when multiple sclerosis drugs are prescribed. The recommended tests for latent tuberculosis are tuberculin and interferon gamma release test. When an anti-tuberculosis treatment is indicated, monitoring should be performed to determine liver enzyme values with consideration of age as well as comorbid conditions such as a history of alcoholism, age, obesity, concomitant hepatotoxic drugs, and history of liver disease. Conclusion: Latent tuberculosis should be considered in patients with multiple sclerosis who are going to be treated with immunomodulatory and immunosuppressant medications. Transaminase level monitoring is required on a periodic basis depending on clinical and laboratory characteristics. In addition to the liver impairment, other side effects should be considered when Isoniazid is prescribed.